The Nun Energicum and the Prefix Conjugation in Biblical Hebrew - Muraoka, Takamitsu (1975)
non-energic forms used with waw-consecutive or ’al; this dichotomy of forms secondary, after loss of volitive ending -a and indicative ending -u.